2019
DOI: 10.1101/742387
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered immunity of laboratory mice in the natural environment is associated with fungal colonization

Abstract: 32The immune systems of free-living mammals such as humans and wild mice display a 33 heightened degree of activation compared with laboratory mice maintained under artificial 34 conditions. Here, we demonstrate that releasing inbred laboratory mice into an outdoor enclosure 35to mimic life in a natural environment alters the state of immunity. In addition to enhancing the 36 differentiation of T cell populations previously associated with pathogen exposure, we found that 37 outdoor release of mice led to an i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 54 publications
(25 reference statements)
0
46
0
Order By: Relevance
“…One intriguing protocol that creates mice that are colonized with natural/wild microbiota is called "rewilding". Graham and coworkers recently reported that when lab mice are transferred to outdoor enclosures where they are exposed to the weather and microbiome that inhabits the soil and vegetation, they display maturation and differentiation of different T cell subsets, increased numbers of circulating granulocytes and changes in intestinal microbiota that are similar to those described above in feral and pet store mice [95][96][97]. When taken together, it is becoming clear that colonization of mice with diverse populations of naturally occurring microorganisms protects them against an environment that contains potentially lethal infectious microbes, inflammogens and carcinogens.…”
Section: Modulation Of Immunity and Inflammation By The Microbiomementioning
confidence: 83%
“…One intriguing protocol that creates mice that are colonized with natural/wild microbiota is called "rewilding". Graham and coworkers recently reported that when lab mice are transferred to outdoor enclosures where they are exposed to the weather and microbiome that inhabits the soil and vegetation, they display maturation and differentiation of different T cell subsets, increased numbers of circulating granulocytes and changes in intestinal microbiota that are similar to those described above in feral and pet store mice [95][96][97]. When taken together, it is becoming clear that colonization of mice with diverse populations of naturally occurring microorganisms protects them against an environment that contains potentially lethal infectious microbes, inflammogens and carcinogens.…”
Section: Modulation Of Immunity and Inflammation By The Microbiomementioning
confidence: 83%
“…In the dirty mouse approach, conventional laboratory mice are exposed to microorganisms that usually do not appear in breeding facilities. This exposure can either be very defined by infecting mice directly with known pathogens [ 229 ] or undefined by either co-housing them with “dirty” non-laboratory mice, such as pet-store mice [ 230 ], or exposing them to a natural environment [ 231 , 232 ]. The latter type of mouse is sometimes referred to as “rewilded”.…”
Section: Implications Of Staphylococcal Host Adaptation For Murinementioning
confidence: 99%
“…Moreover, their guts were also colonized by different fungal communities than those of laboratory mice [ 231 ]. Compared to laboratory mice, dirty mice also present a more mature phenotype of the immune system, as shown for instance by a higher amount of differentiated effector and memory T cells, more serum antibodies and class-switched B cells, a more “adult human being-like” transcription profile, and an increase in mucosally distributed T cells [ 230 , 231 , 232 ].…”
Section: Implications Of Staphylococcal Host Adaptation For Murinementioning
confidence: 99%
See 2 more Smart Citations